A Study on Impromptu Speech Initiation of Programme Hosts Based on Communication Accommodation Theory: The Case of “Hello, Interviewer” - He, Jingfan; Gao, Biao (Journal of Psychology and Psychotherapy Research, 2023)
In recent years, the social situation of choosing a career and employment has become more and more difficult every year, and the mass media has provided a new solution to this dilemma：job-seeking reality shows. In this type of show, the host’s ability to improvise is a critical factor in the show’s success. However, many presenters do not have strong improvisation skills. They cannot reasonably guide the interaction between job seekers, interviewers, and career advisors, resulting in the guests not getting the required information efficiently or the scene getting out of control, ultimately affecting the program’s communication effect. At present, there is a lack of research on how the hosts control the guests’ right to speak and how to trigger the guests to respond in job-seeking reality programmes. Therefore, this paper adopts a qualitative research method and selects the programme “Hello, Interviewer” as the research corpus, drawing on communication accommodation theory in social psycholinguistics, communication, and broadcasting to analyse the forms of improvised speech initiation by the hosts in the job-seeking reality shows. This study divides the overall process of a job-seeking reality show into three stages, including: the opening introduction - low interaction stage, multiple interactions - high interaction stage, and the end of the decision - medium interaction stage. Then, the forms of improvised speech initiation used by the hosts in each stage are summarized in relation to the corpus. The findings of this paper are expected to provide guidance to job-seeking reality show hosts to better master their discourse skills and improve their improvisation skills so as to achieve the most optimal communication effect of the programme.